2013
DOI: 10.1007/s11325-013-0878-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharyngeal fat tissue on the pathogenesis of obstructive sleep apnea

Abstract: In the early stages of OSA, the pharyngeal fat pad seems to play an important role in the development of disease in overweight patients. Furthermore, weight reduction by lifestyle intervention-based programme reduces both central obesity and pharyngeal fat pads, resulting in an improvement of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…However, based on clinical series, mostly conducted in men, NC and WC seem to be more sensitive parameters than BMI for the prediction of OSA (Martinez-Rivera et al, 2008;Seidell, 2010). Furthermore, the amounts of adipose tissue adjacent to the pharyngeal airway and in the intraperitoneal space are directly associated with AHI but not with BMI (Liu et al, 2014;Pahkala, Seppä, Ikonen, Smirnov, & Tuomilehto, 2014;Shelton, Woodson, Gay, & Suratt, 1993). Despite this strong evidence, there is still wide discrepancy as to whether central obesity-related parameters better predict AHI variability in the general population and in clinical cohorts with a high suspicious of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on clinical series, mostly conducted in men, NC and WC seem to be more sensitive parameters than BMI for the prediction of OSA (Martinez-Rivera et al, 2008;Seidell, 2010). Furthermore, the amounts of adipose tissue adjacent to the pharyngeal airway and in the intraperitoneal space are directly associated with AHI but not with BMI (Liu et al, 2014;Pahkala, Seppä, Ikonen, Smirnov, & Tuomilehto, 2014;Shelton, Woodson, Gay, & Suratt, 1993). Despite this strong evidence, there is still wide discrepancy as to whether central obesity-related parameters better predict AHI variability in the general population and in clinical cohorts with a high suspicious of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, obesity may worsen OSA, because of fat deposition surrounding the upper airway. This appears to result in a smaller lumen and increased collapsibility of the upper airway, predisposing to apnea [35,36] . In 36 patients with OSA, Pahkala et al [36] demonstrated that in the early stages of OSA, the pharyngeal fat pad seems to play an important role in the development of disease in overweight patients.…”
Section: Weightmentioning
confidence: 99%
“…Because of increased fat deposition, overweight/obese individuals generally have a more collapsible airway than normal-weight individuals (4)(5)(6)(7)(8), yet the modest relationship between body mass index (BMI) and upper-airway collapsibility (3,9) indicates that some individuals gain weight without major upper-airway compromise.…”
mentioning
confidence: 99%